The Influence of the Work Environment and Organizational Justice on Employee Turnover Intention - Patricia, Dhea; Arninda (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Organizations must pay attention to the factors that affect turnover intention. This study aims to determine the Influence of Work Environment and Organizational Justice on Turnover Intention of PT Hok Tong Employees in Pontianak City. PT Hok Tong Pontianak is a company engaged in the natural rubber remiling industry. This study is an associative study The population in this study is all employees of PT Hok Tong Pontianak. The number of samples was 108 respondents. The data analysis technique used is SPSS 23.0. Based on the results of the research and discussion, it was concluded that the results of the persial influence test of the value of the variable calculation of the work environment did not have a significant effect on the turnover intention of the work environment and organizational fairness, there was a significant influence on the turnover intention